2011
DOI: 10.1007/s00018-011-0837-9
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease: is it a primary immunodeficiency?

Abstract: Inflammatory bowel diseases (IBD) such as ulcerative colitis and Crohn's disease are chronic and relapsing conditions, characterized by abdominal pain, diarrhea, bleeding and malabsorption. IBD has been considered a hyperinflammatory state due to disturbed interactions between the immune system and the commensal bacterial flora of the gut. However, there is evidence that Crohn's disease might be the consequence of a reduced release of pro-inflammatory cytokines and an impaired acute inflammatory response, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 109 publications
1
52
0
1
Order By: Relevance
“…Moreover, it has been found that miRNAs are differentially expressed in ulcerative colitis (UC) and Crohn's disease (CD) [27] , the two main forms of IBD. However, the pathogenesis of IBD still remains enigmatic [28] , but the identification of differentially expressed miRNAs and subsequent understanding of their molecular mechanisms appear to provide new ways to reveal the pathophysiology, discover new diagnostic biomarkers, and develop new therapeutics [27] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been found that miRNAs are differentially expressed in ulcerative colitis (UC) and Crohn's disease (CD) [27] , the two main forms of IBD. However, the pathogenesis of IBD still remains enigmatic [28] , but the identification of differentially expressed miRNAs and subsequent understanding of their molecular mechanisms appear to provide new ways to reveal the pathophysiology, discover new diagnostic biomarkers, and develop new therapeutics [27] .…”
Section: Introductionmentioning
confidence: 99%
“…The most common autoimmune disorders in PADs are immune thrombocytopenic purpura (ITP) and autoimmune hemolytic anemia (AIHA) [7]. Moreover, other diseases including autoimmune thyroid disease [8], type 1 diabetes (T1D) [9], rheumatoid arthritis (RA) [10], systemic lupus erythematosus (SLE) [11], dermatomyositis [12], inflammatory bowel diseases (IBD) [13], alopecia areata [11], vitiligo [8], and glomerulonephritis [14] are also common in PADs due to the lack of self-tolerance [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Pain is usually caused by abdominal cramps, owing to irritation of the nerves by inflammatory cytokines and mediators sensitizing the primary afferents and muscles controlling intestinal contractions (Bielefeldt et al, 2009;Docherty et al, 2011;Glocker and Grimbacher, 2012). Pain may be the only symptom of disease activity in some patients, and about one-sixth of IBD patients are chronically treated with opioids (Edwards et al, 2001;Cross et al, 2005;Lix et al, 2008;Bielefeldt et al, 2009).…”
Section: Discussionmentioning
confidence: 99%